The Rise of Acid Reflux in Asia (Springer India, 2018)
GERD is the most common gastrointestinal disease in the world affecting over 10-20% of the adult population. GERD is often perceived as a Western disease and very little literature available about this disease in the Asian population. With growing obesity and westernization in Asia, the prevalence of GERD is rapidly increasing. With growing morbidity and health care cost there is a significant need for understanding the disease from the Asian perspective. This book would fill the gap in the knowledge on GERD among Asians and will highlight the difference in terms of epidemiology, diagnosis and management of GERD from the Western perspective. The novel imaging, diagnostic modalities and treatment aspects will be essentially highlighted in this book. It also deals about the pathogenesis and risk factors of Asians for the development of GERD which have not been explored before. Another important difference is that the book would be dealing with symptom perception and cultural factors affecting the diagnosis and management of this common disorder. Finally, the surgical outcomes of GERD among Asians will be discussed. Information on these topics is limited.